2000
DOI: 10.1038/modpathol.3880024
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of P53 Mutations of Synchronous Colorectal Carcinomas

Abstract: It is unclear whether synchronous multiple tumors arise from multicentric or monoclonal origins. To verify the multicentric origin of synchronous colorectal carcinomas at a genetic level, immunohistochemical and molecular techniques were used to determine the p53 alterations in individual lesions of synchronous colorectal carcinomas. This study was based on a total of 32 colorectal tumors from 16 patients. Twenty-one of the 32 (66%) advanced tumors examined had positive staining for p53. Single-strand conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
1
20
1
1
Order By: Relevance
“…This gene is considered to be the most prevalent genetic alteration in human neoplasms. Eguchi et al [25] found that in SCRCs, the p53 mutations in left-sided and rectal carcinomas were different from those in right-sided carcinomas (p = 0.04), supporting the idea that SCRCs may be of multicentric origin [26]. In addition, Yalcinkaya et al [27] showed that p53 expression in SCRCs was strongly associated with aggressiveness and poor prognosis; specifically, adenocarcinomas with poor differentiation and deeper invasion had higher expression of p53.…”
Section: Pathological Characteristicsmentioning
confidence: 99%
“…This gene is considered to be the most prevalent genetic alteration in human neoplasms. Eguchi et al [25] found that in SCRCs, the p53 mutations in left-sided and rectal carcinomas were different from those in right-sided carcinomas (p = 0.04), supporting the idea that SCRCs may be of multicentric origin [26]. In addition, Yalcinkaya et al [27] showed that p53 expression in SCRCs was strongly associated with aggressiveness and poor prognosis; specifically, adenocarcinomas with poor differentiation and deeper invasion had higher expression of p53.…”
Section: Pathological Characteristicsmentioning
confidence: 99%
“…Although these big polyps were not malignant, if they had been found postoperatively as with conventional IACI method, another laparotomy might have been performed because of the size and risk of perforation in the case of endoscopic removal. The incidence of two or more primary colorectal carcinomas has been estimated to range between 2% and 11% of all carcinomas in the colon and rectum [1,6,9,11,18,27].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the most current estimates of incidence are still considered to be inaccurate since not all tumors are discovered clinically and the number of related population studies is still relatively low. Genetic and molecular pathways associated with colorectal cancer synchronicity, such as microsatellite instability, altered expression of p53, and gene promoter methylation have received increasing attention in the pertinent literature (15)(16)(17)(18)(19)(20). In addition, distinct clinical features of patients with multiple colorectal lesions (such as age, male gender, metastasis rates) have been studied, yet their prognostic signifi cance remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%